Understanding Technology Literacy: The Characteristics of ICT Literacy Vocational Teachers - S, Saripudin; Sumarto, S; A Juanda, E; Ghafar Abdullah, Ade; A, Ana (International Journal of Engineering and Technology, 2018)
Information and Communication Technology (ICT) Literacy is the ability to use digital technology, communication tools and/or networks to define, access, manage, integrate, evaluate, create and communicate information well and legally toward a knowledgeable society. This literature study looks at the level of ICT literacy of vocational high school (SMK) teachers. The purpose is to determine the ICT literacy skills of vocational teachers in integrating and assessing ICT learning. The method used is literature review by searching and selecting articles / journals with suitable topics which then are proceed to analysis. The results of this literature study are to look the ICT literacy of vocational school teachers in using technology to conduct learning in the classroom.Â Â